Boosting widespread adoption of sustainable agriculture – New metrics and the role of science - Estrada-Carmona, Natalia; Sharma, Sunayana; Rana, Jai Chand; Lal, Kuldeep Kumar (Indian Society of Plant Genetic Resources (ISPGR), 2022)
Adapting to new climatic, social, and environmental realities demands deep and massive transformative changes in how humans manage, perceive, and relate with terrestrial and aquatic productive systems. In India, agriculture production is challenged by degraded soils, scarce and contested water, fragmented and degraded seminatural habitats, social conflict, and more frequent extreme events. Existing political will is enabling the adoption of sustainable agriculture. However, the pace and the extent of the adoption of promising strategies, practices, and approaches for achieving sustainable and resilient agriculture remains sparse. Accelerating a socially just transformation to sustainability in India requires a new systems-oriented, multidisciplinary, human well-being-centered research agenda. Specifically, the new agenda can expand, contest and reevaluate agriculture performance’ in terms of how is evaluated and measured at the farm and landscape level. The new evidence will be critical for learning, innovating and re-designing sustainable, multifunctional and resilient agricultural landscapes.